1995
DOI: 10.1074/jbc.270.47.28153
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Diamidine Drugs by the P2 Nucleoside Transporter in Melarsen-sensitive and -resistant Trypanosoma brucei brucei

Abstract: The African trypanosome, Trypanosoma brucei brucei, possesses at least two nucleoside transporter systems designated P1 and P2, the latter being implicated in the selective uptake of melaminophenyl arsenical drugs. Since arsenical-resistant trypanosomes show cross-resistance in vivo to aromatic diamidines, we have investigated whether these drugs are also substrates for the P2 nucleoside transporter. In melarsen-sensitive T. b. brucei, the diamidines, including the commonly used trypanocides, pentamidine and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(62 citation statements)
references
References 24 publications
(31 reference statements)
2
60
0
Order By: Relevance
“…23 In each case, the possibility emerged of introducing substituents at positions 4–7 of the pyrrolopyridine template to direct substituents into hydrophobic pockets near Cys168, Leu209, Pro210, Met213, and Trp221. The requirement for transport into trypanosomes and the possibility that the specific transporters found in trypanosomes that prefer 4-aminopyrimidine substrates might concentrate the inhibitors advantageously were also considered; 20,21 2,4-diaminopyrimidines were therefore considered to be important substructures at the outset of this work. Recognizing that physicochemical properties also play an important role in the biological activity of substituted pyrimidines, 4-alkoxy and 4-alkylamino substituents were investigated.…”
Section: Compound Designmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In each case, the possibility emerged of introducing substituents at positions 4–7 of the pyrrolopyridine template to direct substituents into hydrophobic pockets near Cys168, Leu209, Pro210, Met213, and Trp221. The requirement for transport into trypanosomes and the possibility that the specific transporters found in trypanosomes that prefer 4-aminopyrimidine substrates might concentrate the inhibitors advantageously were also considered; 20,21 2,4-diaminopyrimidines were therefore considered to be important substructures at the outset of this work. Recognizing that physicochemical properties also play an important role in the biological activity of substituted pyrimidines, 4-alkoxy and 4-alkylamino substituents were investigated.…”
Section: Compound Designmentioning
confidence: 99%
“…19 In addition, pyrrolopyrimidines bring with them the advantage of carrying a pharmacophore with structural similarity to the recognition motif of the parasite’s P2 aminopurine transporter, 20 a membrane protein capable of accumulating its substrates to internal levels that exceed external concentrations up to a thousand-fold. 21 Previously, we reported that a number of heterocyclic compounds including substituted pyrrolopyrimidines and furopyrimidines are inhibitors of PTR1 from Trypanosoma brucei and Leishmania major . (7,22) Here, we use structure-based design on the pyrrolopyrimidine template, taking into consideration appropriate synthetic strategies, to obtain compounds with anti-trypanosomal activity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Dosing for early-stage disease consists of a series of 7–10 intramuscular injections; however, shorter dose regimens are being explored [10]. African trypanosomes have a nucleoside (adenine/adenosine: P2) transporter that takes up pentamidine, resulting in the concentration of the agent at levels many times that in plasma [12, 13]. Recent studies have found two other transporters, besides P2, that also transport pentamidine and may be responsible for 50% of its uptake [14].…”
Section: Current Chemotherapymentioning
confidence: 99%
“…However, melarsoprol and related arsenicals may also bind to other sulfhydryl-containing agents in the cell, including dihydrolipoate and the closely adjacent cysteine residues of many proteins. Similar to pentamidine and diminazene, melarsoprol uptake into African trypanosomes has been attributed to the P2 purine nucleoside transporter; thus, significant levels can be concentrated in the cell from a low external (plasma) concentration [12, 13]. Although most laboratory-generated melarsoprol-resistant strains have lost or modified the P2 transporter, clinical isolates appear to have retained uptake capacity [14].…”
Section: Current Chemotherapymentioning
confidence: 99%
“…Carter and Fairlamb characterized an unusual transporter, called P2 (3). They found that in addition to the uptake of adenosine and adenine, the P2 transporter also was involved in the uptake of melaminoarsenicals, such as melarsen oxide, and diamidines, such as pentamidine (4). It was established that melamines and benzamidines are substrates for the P2 transporter but not significantly so for mammalian transporters.…”
mentioning
confidence: 99%